LUNG CANCER SURVIVAL ANALYSIS WITH PROPORTIONAL HAZARD MODEL: Abstract - Nata nasaruddin, M.
Abstract: In this thesis, will be analysed the survival data concerning with variables that related to lung cancer desease where this variables assumed to have an effect on time to event. Proportional Hazard Model will be used to analyse this problem where this model can allow us to quantify the relationship between the time to event and a set of explanatory variables. After analysis, writer obtained the conclusion that Karnofsky Performance Score ( Z3) can influence the survival rate of patient of lung cancer desease.